Risk of type 2 diabetes mellitus among women with gestational diabetes mellitus in semi-urban area, Thiruvallur district, Tamil Nadu: a case control study - Pushparani, Joy Patricia; Yazhini, M.; Priya, K. Caroline (International Journal Of Community Medicine And Public Health, 2020)
Background: Gestational diabetes mellitus (GDM) is one of the risk factors associated with type 2 diabetes mellitus. Hence early detection by screening and management of GDM is very essential to reduce the burden of type 2 diabetes. Objectives was to evaluate the strength of association of GDM and type 2 diabetes among women aged 30 to 35 years in Thiruvallur District, to find the association of other risk factors with type 2 diabetes. Methods: A study was conducted among 160 women with 44 cases and 116 controls aged 30-35 years attending NCD clinics in Thiruvallur District between March and September 2016. The cases and controls were matched for age and time period between last delivery and the time of screening as 5 years or more. GDM exposure was ascertained if their venous blood glucose levels during their antenatal and postpartum period exceeded the oral glucose tolerance test criteria recommended by national guidelines. Results: In the study it was found that women with history of GDM are 4.65 times higher at risk of developing type 2 diabetes. There was significant association (p=0.000) between type 2 diabetes and risk factors like family history of diabetes, co-morbidities like hypertension, hypothyroidism. Conclusions: Gestational diabetes is a predictor of type 2 diabetes, as the women are registered in the pregnancy and infant cohort monitoring and evaluation system, it has the potential to identify women at risk of type 2 diabetes and intervene at the earliest.